Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2005
DOI: 10.1111/j.1365-2583.2005.00576.x
|View full text |Cite
|
Sign up to set email alerts
|

The Tribolium chitin synthase genes TcCHS1 and TcCHS2 are specialized for synthesis of epidermal cuticle and midgut peritrophic matrix

Abstract: Functional analysis of the two chitin synthase genes, TcCHS1 and TcCHS2 , in the red flour beetle, Tribolium castaneum , revealed unique and complementary roles for each gene. TcCHS1-specific RNA interference (RNAi) disrupted all three types of moult (larval-larval, larvalpupal and pupal-adult) and greatly reduced whole-body chitin content. Exon-specific RNAi showed that splice variant 8a of TcCHS1 was required for both the larvalpupal and pupal-adult moults, whereas splice variant 8b was required only for the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

23
293
4
3

Year Published

2005
2005
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 291 publications
(323 citation statements)
references
References 26 publications
(35 reference statements)
23
293
4
3
Order By: Relevance
“…2 C and E). Molting defects in TcKnk dsRNA-treated beetles closely resembled those previously observed after dsRNA-mediated knockdown of T. castaneum chitin synthase A (TcChs-A), which is essential for cuticular chitin synthesis (12). Quantitative chemical analysis revealed that insects subjected to RNAi for TcKnk were severely deficient in total chitin, comparable to insects in which chitin synthesis was prevented by RNAi for TcChs-A (Fig.…”
Section: Resultssupporting
confidence: 57%
See 1 more Smart Citation
“…2 C and E). Molting defects in TcKnk dsRNA-treated beetles closely resembled those previously observed after dsRNA-mediated knockdown of T. castaneum chitin synthase A (TcChs-A), which is essential for cuticular chitin synthesis (12). Quantitative chemical analysis revealed that insects subjected to RNAi for TcKnk were severely deficient in total chitin, comparable to insects in which chitin synthesis was prevented by RNAi for TcChs-A (Fig.…”
Section: Resultssupporting
confidence: 57%
“…dsRNA-treated pharate pupal and pharate adult insects were collected for chitin content analysis. Chitin content was measured with a modified Morgan-Elson method as described previously (12). Insects treated with dsRNA for T. castaneum Vermilion (TcVer) and TcChs-A were used as negative and positive experimental controls, respectively (n = 5).…”
Section: Methodsmentioning
confidence: 99%
“…Whereas tyrosinases, which are oxidases that contain two copper ions and catalyze the oxidation of ortho-diphenols, have been studied extensively for their roles in melanization, wound healing, and insect immunity (7,(9)(10)(11), less information is available about the importance in insect developmental physiology of laccases, which are oxidases that contain four copper ions and have ortho-and para-diphenol oxidizing activities (4,12). To establish the involvement of either or both of these phenoloxidase genes in insect cuticle tanning, RNA interference (RNAi) experiments were performed by using the red flour beetle Tribolium castaneum, an economically important agricultural pest species that is exquisitely sensitive to dsRNAmediated posttranscriptional gene silencing (13,14). The results presented here demonstrate that a specific laccase gene plays the major if not exclusive role in the tanning of larval, pupal, and adult cuticles of T. castaneum.…”
mentioning
confidence: 99%
“…10,11) To date, two CHS genes have been identified in the genome of the fruit fly Drosophila melanogaster, 12) the tobacco hornworm Manduca sexta, 13) and the red flour beetle Tribolium castaneum. 14) In T. castaneum, for example, CHSA (also called CHS1) is responsible for synthesizing epidermal cuticle, whereas CHSB (CHS2) is responsible for synthesis of the midgut peritrophic matrix. 14) Meanwhile, a mite growth inhibitor, etoxazole [4-(4-tertbutyl-2-ethoxyphenyl)-2-(2,6-difluorophenyl)-1,3-oxazoline], belonging to Group 10B in the IRAC MoA classification, 15) has been reported to induce molting defects, reduce chitin content, and inhibit the incorporation of radiolabeled GlcNAc into chitinous material in the fall armyworm Spodoptera frugiperda, as was also observed after benzoylurea treatment.…”
Section: Introductionmentioning
confidence: 99%
“…14) In T. castaneum, for example, CHSA (also called CHS1) is responsible for synthesizing epidermal cuticle, whereas CHSB (CHS2) is responsible for synthesis of the midgut peritrophic matrix. 14) Meanwhile, a mite growth inhibitor, etoxazole [4-(4-tertbutyl-2-ethoxyphenyl)-2-(2,6-difluorophenyl)-1,3-oxazoline], belonging to Group 10B in the IRAC MoA classification, 15) has been reported to induce molting defects, reduce chitin content, and inhibit the incorporation of radiolabeled GlcNAc into chitinous material in the fall armyworm Spodoptera frugiperda, as was also observed after benzoylurea treatment. 16) Although both benzoylureas and etoxazole are known to inhibit chitin synthesis, their molecular mode of action has been an enigma.…”
Section: Introductionmentioning
confidence: 99%